EKSPLORASI MAKNA AN-NAJM PADA SURAH AR-RAHMAN AYAT 6 SEBUAH KAJIAN TAFSIR KONTEMPORER - Syeh Sarip Hadaiyatullah; Ferdy Yusuf Matondang; Fabian Daffa Tresna (Yayasan Baitul Hikmah al-Zain, 2025)
The Qur'an is a linguistic miracle that is rich in linguistic meaning and beauty. Each word in the Qur'an not only has a literal meaning but also a contextual depth that invites further study. The data used includes primary sources in the form of Qur'an texts and secondary sources such as classical and modern books of interpretation, This research uses reflective methods to connect interpretation with wisdom that Muslims can take in understanding the signs of Allah's power in the universe. This study aims to explore the meaning of the word an-najm in Surah Ar-Rahman verse 6 through three main focuses: the linguistic meaning of an-najm, the opinion of the mufassir, and the benefits or wisdom that can be drawn from the verse. The scholars agree that what is meant by (الشَّجَرُ) is trees that have trunks, such as durian trees, mangoes and so on. However, commentators differ on the meaning of ( لنَّجْمُ). There are two opinionsFirst, it means that plants that do not have stems, such as kale, vegetables. This means that Allah SWT explains about the trees, whether they have a trunk or not, all bow down and prostrate to Allah SWT. Second, it means celestial bodies, namely stars. This second opinion is an opinion that was strengthened by Ibn KatsirAyat as a reminder for humans to submit to Allah, maintain the balance of nature, and be grateful for all the blessings given. Tafakkur towards nature through this verse can increase faith and strengthen spiritual awareness. Islam as a perfect religion certainly has the basics of teachings for its people that are related to the natural environment.